2019
DOI: 10.1111/1365-2656.13095
|View full text |Cite
|
Sign up to set email alerts
|

Demographic plasticity facilitates ecological and economic resilience in a commercially important reef fish

Abstract: 1. Variation in life-history characteristics is evident within and across animal populations. Such variation is mediated by environmental gradients and reflects metabolic constraints or trade-offs that enhance reproductive outputs. While generalizations of life-history relationships across species provide a framework for predicting vulnerability to overexploitation, deciphering patterns of intraspecific variation may also enable recognition of peculiar features of populations that facilitate ecological resilie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 62 publications
(85 reference statements)
3
27
0
Order By: Relevance
“…Maximum sizes and ages at lower latitudes are expected to be lower, since age-based demography of reef fishes varies with sea temperature (e.g. Choat et al 2003, Robertson et al 2005, Taylor & Pardee 2017, Taylor et al 2019. Despite potential differences in longevity between individuals in our study area and in the Abrolhos Bank, age and size of maturation were comparable between these regions (Table 1).…”
Section: Discussionmentioning
confidence: 82%
“…Maximum sizes and ages at lower latitudes are expected to be lower, since age-based demography of reef fishes varies with sea temperature (e.g. Choat et al 2003, Robertson et al 2005, Taylor & Pardee 2017, Taylor et al 2019. Despite potential differences in longevity between individuals in our study area and in the Abrolhos Bank, age and size of maturation were comparable between these regions (Table 1).…”
Section: Discussionmentioning
confidence: 82%
“…given that historical collections were made on hook and line (Heupel et al, 2010;Mapstone et al, 2004) Differences in environment and habitat often manifest as changes in lifetime growth (Choat & Robertson, 2002;Mora, 2015;Taylor et al, 2019), but growth profiles and length-at-age estimates for P. leopardus and P. laevis were similar between regions. Stable isotope (Hempson et al, 2017;Matley et al, 2017) and stomach content (Kingsford, 1992) analyses have demonstrated that coral grouper are capable of feeding on a range of prey items and may modify their diet following local disturbances (Wen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, we emphasize caution when comparing growth parameters among models when sizes at settlement were not constrained to a common value. Broad spatial studies that span large environmental gradients ( e.g ., Trip et al ., 2008) or the application of biochronology techniques ( e.g ., Taylor et al ., 2019) may further improve the resolution of environmental‐driven variation in growth of coral grouper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While numerous studies have examined the implications of increasing temperature and temperature variability on coral reef fish growth (e.g. Munday et al 2008;Messmer et al 2017;Taylor et al 2019), to our knowledge there has been no investigation of the combined effect of increasing temperature and salinity on coral reef fish demography. This is despite the evidence of synergism between the two stressors (Claireaux and Lagarde 1999;Jian et al 2003) and the likely occurrence of both stressors in already dry regions and hyper-saline (sensu saltier than ocean salinity) semienclosed seas in the near future (such as the Arabian Gulf, Red Sea and Mediterranean Sea) (Durack et al 2012;Skliris et al 2014;Zika et al 2018).…”
Section: Discussionmentioning
confidence: 99%